Glad Adventures, Tragedies, Silences: Remembering and Forgetting Wars for Empire in Canada and the United States - Teigrob, Robert (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d’études canadiennes, 2012)
This article surveys a century of U.S. writing on the War of 1898, and Canadian writing on the South African War, in order to contrast national attitudes toward international conflict. While Canadians tend to view their American neighbours as more fond of military exploits, a comparison of the historical representation of these remarkably similar fin de siècle conflicts finds a greater willingness among American popular and scholarly analysts to impugn their nation’s motivations in the War of 1898, and to call attention to aspects of the battle that reflect poorly on their nation’s self-image. Canadians, for their part, have tended to steer clear of controversial aspects of the South African War, or to ignore it altogether – over the course of a century that has otherwise witnessed an ongoing fascination with Canada’s participation in foreign conflicts. I suggest that this diffidence has roots in English Canada’s historical affections for imperialism, faith in government, and ethnic and cultural homogeneity, the latter of which has seen much of the military history of Canada recounted by individuals of similar identities and points of view.